Social Media Influences Holiday Travel Decisions : A Rationale for Profound Analysis - Singh, Neha; Yadav, Pooja (Prabandhan: Indian Journal of Management, 2018)
Social media is emerging as an informative tool for business and India is witnessing an exceptional growth in the number of users on social media. Travellers use various information sources to plan their holidays and social media is actively used by them in different stages of holiday travel. Research studies have indicated that social media has an impact on holiday travel decisions, although it varies across the geographical boundaries. Few studies have indicated that social media is used during the planning stage of a holiday, while a few indicated that it is used after a holiday. This research attempted to find or explore the role and impact of social media on consumers’ travel decision making process. It discussed the approach used by certain authors - whether it was social media application specific or specific to one aspect of travel decision, that is, a destination or hotel. This paper also attempted to explore the studies which indicated that there was a correlation between social mediaâ€™s level of influence and the travel decision making process at different travel stages, that is, before, during, and after the consumption of a holiday.